Schizonticidal effect of a combination of Amaranthus spinosus L. and Andrographis paniculata Burm. f./Nees extracts in Plasmodium berghei-infected mice (Faculty of Medicine Universitas Indonesia, 2012)
Background: Amaranthus spinosus and Andrographis paniculata are traditionally used as antimalarial herbs, but the combination of both has not yet been tested. The aim of this study was to determine the schizonticidal anti-malaria effect of a combination in Plasmodium berghei-infected mice. Methods: Male mice (Balb/c strain) weighing 28-30 g, 7-8 weeks old, were randomly devided into 5 groups of 4 animals each. Group A: controls (nil) and 4 treatment groups (B, C, D, and E). Group B: Amarathus 10 mg/kgBW, group C: Andrographis 2 mg/kgBW, group D: combination of Amaranthus + Andrographis 10 mg + 2 mg/kgBW. All treatment with plant extracts was administered orally, once per day for 7 days. Group E was given chloroquine 10 mg/kgBW, once a day orally, for 3 days. Results: The body weigh increased only in group D, hemoglobin concentration increased significantly vs controls (p < 0.05) in treatment groups C, D, and E, and blood schizonticidal activity was seen in all treatment groups, highest at almost 90% in groups D and E. Survival rate was 100% in all groups. Conclusion: The combination of Amaranthus and Andrographis (10 mg + 2 mg/kgBW) exerts the same blood schizonticidal activity as chloroquine 10 mg/kgBW. (Med J Indones. 2012;21:66-70)